Зависимость трематодофауны водно-болотных птиц от питания - Искова, Н.И. (Вестник зоологии, 1970)
Показана зависимость трематодофауны водно-болотных птиц Северо-Западного Причерноморья от характера их питания. Наиболее разнообразный видовой состав трематод (76 видов) выявлен у птиц, питающихся в основном беспозвоночными — промежуточными хозяевами паразитов, менее разнообразный (35 видов) — у птиц-ихтиофагов. Однако экстенсивность и интенсивность заражения последних были выше, чем других птиц. A dependence is shown of trematode fauna of water-bog birds from the North-Western Black sea area on the nutrition character. The most various specific composition of trematodes (76 species) is detected in birds, feeding mainly on invertebrates — intermediate hosts of trematodes, and the least variable trematode composition (35)—in birds-ichthyophages. But extensity and intensity of infection in latter were higher than in other birds. It is explained by nutrition of birds-ichthyophages with monotonous fish food and usually by the higher infection of fish with metacercaria of trematodes as compared with invertebrates. Birds, feeding on the mixed (vegetable and animal) food occupy an intermediate position according to specific composition of trematodes found in them. In those birds both trematodes, metacercaria of which develop in invertebrates, and such species, invasion stages of which (adolescaria) are encysted on plants are found.